Instruction in Islamic Religious Education: Teacher-Student Communication at Padangsidimpuan State 1 High School - Suwandi Simangunsong; Nurzakiah Simangunsong; Namiroh Lubis (Yayasan Zia Salsabila, 2024)
The purpose of this study is to examine how teachers communicate with students at SMA Negeri 1 Padangsidimpuan during Islamic Religious Education (PAI). This kind of research combines a literature study methodology with a qualitative approach. Quotations for data sources are taken from reliable websites like SINTA and Google Scholar. Data triangulation was then used to examine and validate the data. The study's findings indicate that, first, there needs to be communication between PAI teachers and deputy principals in the field of curriculum development, particularly when it comes to carrying out lesson plans, syllabi, and follow-up student assessments. Secondly, when PAI teachers communicate about PAI material, they truly take into account the students' backgrounds, abilities, and the fundamental skills that all teachers should possess, such as the ability to explain complex material in a way that students can easily understand and accept.